Return to play after treatment of shoulder labral tears in professional hockey players. Issue 2 (2nd April 2016) - Rangavajjula, Ashwin; Hyatt, Adam; Raneses, Eli; McCrossin, Jim; Cohen, Steven; DeLuca, Peter
ABSTRACT: Objectives : Shoulder labral injuries in professional hockey players are often treated surgically to minimize missed ice time. Previous studies have shown that post-operative outcomes in these players are favorable, although they have not specifically focused on athletic performance and time to return to sport. Our objective was to report time to return to play and post-operative on-ice performance metrics after shoulder labral repair in professional ice hockey players. Methods : We performed a retrospective review of the clinical records of all professional hockey players (NHL) who underwent arthroscopic shoulder labral repair by one surgeon between January 2004 and December 2008. Operative data included labral injury type, number of anchors used, concomitant pathology, and complications. Player information included position, shooting hand, games played before and after surgery, date of return to play (RTP), time on ice (TOI) and shots on goal before and after surgery. Paired sample t-test and independent sample t-tests or their non-parametric equivalents were used to compare pre-and post-operative player performance variables using the SPSS statistical package. Results : Eleven NHL Players (13 shoulders) were included in the study. The average follow-up was 19.4 months (12.7–37 months, SD 7.4) and average age was 29 years (20–36, SD 5.1). Of the 13 shoulders, there were various types of labral tears including three Bankart tears, three superior (SLAP) tears, two posterior tears, three combined anterior/posterior tears, and two panlabral tears. All 11 players returned to play (RTP) after surgery at an average time of 4.3 months. There were no significant differences between time to RTP for players with dominant-sided injuries (4.2 months) and non-dominant injuries (4.6 months), p = 0.632. Five players had increased time-on-ice (TOI) and five players had decreased TOI after surgery, though this difference was not significant (p = 0.3804). On average, the shots on goal per game played (SOG/GP) decreased by 0.13 after surgery which was not significantly different (p = 0.149). There were no post-operative complications observed. Conclusion : Professional ice hockey players can safely return to full competition at an average of 4.3 months after arthroscopic shoulder labral repair without significant decline in player performance.